A study on the effects of tyre to vehicle acoustical comfort in passenger car cabin - Ahmad Kadri, Junoh; Wan Zuki Azman, Wan Muhamad; Zulkifli, Mohd Nopiah, Assoc. Prof. Dr.; Mohd Jailani, Mohd Nor, Prof. Ir. Dr.; Ahmad Kamal Ariffin, Mohd Ihsan, Prof.; Mohammad Hosseini, Fouladi, Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/